Predicting the Intention to Implement Green Practices by Small and Medium Sized Hotels in South Africa - MASEBE, Proceed Lerato; FATOKI, Olawale (Journal of Environmental Management and Tourism, 2023)
The study examined the intention to implement green practices by small and medium sized hotels in South Africa by extending the Theory of Planned Behaviour (TPB). Three personal factors namely moral norms, response efficacy and environmental concern were used to extend the TPB. In addition, the study examined if intention predicted the implementation of green practices. A quantitative approach was utilised, and a self-administered questionnaire was used for the collection of data from hotel managers and owners. The Partial Least Square Structural Equation Modelling (PLS SEM) was utilised for the analysis of data and testing of hypotheses. The results of the empirical study indicated that attitude, moral norms and response efficacy have significant positive relationships with green practice intention. In addition, intention is a predictor of the implementation of green practices. The implication of the study is that the extended TPB can help to improve the understanding of the intention to implement green practices by small and medium sized hotels. From a theoretical perspective, the study developed a model on the intention to implement green practices by extending the TPB by three individual factors namely moral norms, response efficacy and environmental concern. Empirically, the study provides a clear understanding of the predictors of the intention to implement green practices.